Musculoskeletal symptoms and job strain among nursing personnel: a study over a three year period. Issue 9 (September 1997) - Josephson, M; Lagerström, M; Hagberg, M; Wigaeus Hjelm, E
Abstract : OBJECTIVES: To examine the variation of symptoms from the neck, shoulders, and back over a three year period among female nursing personnel and the relation between job strain and musculoskeletal symptoms. METHODS: At a county hospital the female nursing personnel answered a questionnaire at baseline and then once a year over a period of three years. There were 565, 553, 562, and 419 subjects who answered the questionnaire at the first, second, third, and fourth survey, respectively. Of the study group, 285 nursing personnel answered the questionnaire on four occasions. Ongoing symptoms of the neck, shoulders, and back were assessed by means of a 10 point (0-9) scale with the verbal end points "no symptoms" and "very intense symptoms." Cases were defined as nursing personnel reporting ongoing symptoms, score > 6, from at least one of the body regions. For assessments of job strain, a Swedish version of Karasek and Theorell's model was used. RESULTS: Of the 285 subjects, 13% were defined as cases at all four assessments, and 46% varied between cases and not cases during the study period. In the repeated cross sectional surveys the estimated rate ratio (RR) for being a case was between 1.1 and 1.5 when comparing the group with job strain and the group without job strain. For the combination of job strain and perceived high physical exertion the estimated RR was between 1.5 and 2.1. When the potential risk factors were assessed one, two, or three years before the assessment of symptoms the estimated RR for becoming a case was between 1.4 and 2.2 when comparing the group with job strain and the group without job strain. CONCLUSION: Almost half of the healthcare workers varied between being a case and not, over a three year period. The analysis indicated that job strain is a risk factor for musculoskeletal symptoms and that the risk is higher when it is combined with perceived high physical exertion.